FAKTOR-FAKTOR YANG MEMPENGARUHI PENGETAHUAN IBU TENTANG PERAWATAN BALITA DENGAN PNEUMONIA DI RUMAH - ", Norsusanti "; Amir, Yufitriana "; ", Bayhakki " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractPneumonia is an infection that occurs in the lungs that can be caused by bacteria, viruses or fungi. proper handling of pneumonia at home by parents can reduce dead mortality from pneumonia. This study aimed to determine factors related to the the factors that affect the mother in the care of infants with pneumonia at home. The research used descriptive correlation design with retrospektif approach. The sample are 60 respondent was non probability sampling and purposive sampling with selected base inclusion criteria. Instrument used in the study was questionnaires that on validity and reliability test. The analysis used are univariate and bivariate with chi square test. The results showed that occupational factors (p value 0,005) and the resources (p value 0,006) < α (0,05) there is a correlation with mother’s knowledge about pneumonia toddler care at home. The aged factor (p value 0,866), education (p value 0,405) and earnings (p value 0,545) > α (0,05) the result show there is no correlation with mother’s knowledge about pneumonia toddler care at home. The results of this study is necessary to improve health promotion about caring children with pneumonia at home. Keywords: Knowledge, toddler, pneumonia